Examining the effects of financial performance, corporate governance, and corporate social responsibility on company value amid the COVID-19 pandemic - Adelia Febriani; Muhammad Fahmi; Nina Febriana Dosinta (Journal of Enterprise and Development (JED), 2024)
Purpose — The study aimed to examine the impact of financial performance, good corporate governance, and corporate social responsibility on the value of SRI Kehati index companies during the COVID-19 pandemic, specifically from 2020 to 2022.Method — This study employs a causal quantitative analysis approach to determine the cause-and-effect relationship between the independent and dependent variables. Data were collected from the annual reports and sustainability reports of companies listed on the IDX and included in the SRI Kehati index during the COVID-19 pandemic. The analysis technique used in this study is panel data regression analysis, encompassing multiple companies and years. After data collection, Eviews 12 is used to process the data.Result — The findings of this study indicate that profitability has a significant impact on the value of SRI Kehati index firms. However, leverage, institutional ownership, and corporate social responsibility do not have a significant effect on the value of these companies.Novelty — The originality of this study stems from its sample, which consists of companies included in the SRI Kehati index listed on the IDX. The conclusions of this study also contradict earlier research. Previous studies have found that leverage, institutional ownership, and corporate social responsibility significantly impact firm value. However, in this study, these three factors did not affect company value.